La Celestina (1499) fice centuries later: celestinesque echoes in Tiempo de Silencio (1962) - Irene López Rodríguez (Celestinesca, 2021)
Although five centuries have gone by between the publication of La Celestina (1499) and Tiempo de silencio (1962), there are echoes of the medieval text in the post-war novel, particularly as regards the characterization of its main prostitute. In fact, to portray Doña Luisa Luis Martín Santos uses Fernando de Rojas' Celestina as a model. The literary pictures of both procuresses stand out by their striking similarities in terms of their physical and psychological descriptions, onomastics, several jobs, homes and attires, associations with necromancy and the devil as well as the rest of the characters surrounding them. Following in the footsteps of his medieval predecessor, the contemporary novelist resorts to the world of prostitution in order to reflect the deep crisis of values that ravage the Spanish society during Franco's dictatorship.